Non-operative Management for Uncomplicated Appendicitis: An Option to Consider - Abbo, Olivier; Trabanino, Carmen; Pinnagoda, Kalitha; Ait Kaci, Amir; Carfagna, Luana; Mouttalib, Sofia; Combelles, Sophie; Vial, Julie; Galinier, Philippe (European Journal of Pediatric Surgery, 2018)
Aim The main goal of our study was to assess a 7 days long course of antibiotics for acute uncomplicated appendicitis.Materials and Methods From March 2014 to November 2015, all patients diagnosed with acute appendicitis have been considered to be treated by only antibiotics. Inclusion criteria included clinical (tenderness), biological (C-reactive protein [CRP] < 50), and radiological features (diameter > 6 mm). All patients were treated with intravenous amoxicillin and clavulanic acid (100 mg/kg/day) for 2 days (six doses). At the end of the treatment, clinical and paraclinical examinations included blood samples at day 7 and ultrasound (US) scan at 3 months.Results A total of 166 patients were treated and followed up prospectively during the study period. Mean age at diagnosis was 10.8 ± 0.6 years. All children, but four were discharged with a clinical improvement after 48 hours and six intravenous antibiotics injection according to our protocol. Four children required surgery during the initial hospitalization period.Initial ultrasound scan showed a mean diameter of 7.85 ± 1.6 mm, with inflamed fat in 124 patients (74.7%). At Day 7, the diameter was 5.2 ± 1.6 mm (p < 0.0001).During a median follow-up of 18.8 months (3.5–18), 22 patients (13.25%) had to be managed for a novel episode of acute appendicitis after a median period of 138 days (13–270). None had to be managed for a complicated appendicitis.Conclusion Non-operative treatment (NOT) is a safe alternative for the management of uncomplicated acute appendicitis in children. Further study should be conducted to determine relapse risk factors.
Keywords: appendicitis; non-operative management; antibiotics